The Instructional Media to Teach English for Young Learner - Blessy Wilar (Journal of English Language Teaching, Literature and Culture, 2022)
The purpose of this article is to discover the applicable Instructional Media to help teacher in teaching English for young learners for different situations. This study used library research, which this research is a series of activities related to the method of collecting library data. Instructional Media is a facilitation used to implement instruction given by the teacher. It is also facilitate students to have a better understanding to the material. In a similar vein Adegun (1997) says instructional media are things which are intended to help the teacher to teach more effectively and enable the students to learn more readily. Considering the characteristics of young learner, the media used have to be interest for students. From the discussion, there are five medias can be used to teach English for young learners, such as realia, pictures, boards, flipcharts, and Internet.